Risk factors for coexistence of fluoroquinolone resistance and ESBL production among Enterobacteriaceae in a Greek university hospital. - Katsandri, A; Avlamis, A; Vasilakopoulou, A; Mela, V; Kosmidis, C; J Papaparaskevas; Petrikkos, G L (J Chemother, 2008)
The purpose of this study was to identify risk factors for fluoroquinolone resistance (QR) among ESBL- producing Enterobacteriaceae causing nosocomial infections. The study was conducted in Laikon General Hospital in Athens, Greece, during the period January 2004 - January 2005. Epidemiological and clinical data were collected from the medical charts of the patients diagnosed with nosocomial infections due to an ESBL-producing Enterobacteriaceae. QR was 60% among the 84 ESBL-producing Enterobacteriaceae isolates. Infection from QR-ESBL bacteria was associated with increased hospital stay (p=0.028); QRESBL bacteria were isolated later during hospitalization than fluoroquinolone susceptible (QS)-ESBL (p=0.089); factors associated with QR were immune-deficiency (p=0.047), previous use of carbapenems (p=0.08) and fluoroquinolones (p=0.067), and admission to the Transplantation Unit (p=0.047). In addition, QR-ESBL bacteria were more likely to be resistant to co-trimoxazole (p<0.001), gentamicin (p=0.054) and tobramycin (p=0.004). Logistic regression analysis indicated that admission to the transplantation unit was an independent risk factor for infection due to a QR-ESBL isolate. Results of this study question ciprofloxacin's usefulness as a valid alternative to carbapenems in our hospital for the treatment of infections due to ESBL-producing bacteria. In addition strategies for addressing the QR-ESBL situation should focus on limiting fluoroquinolone and carbapenem consumption and emphasize on barrier precautions in patients with longer hospitalization, immunosuppression, or admission to the transplantation unit.
Keywords: Anti-Bacterial Agents; beta-Lactamases; Cross Infection; Drug Resistance, Multiple, Bacterial; Enterobacteriaceae; Female; Fluoroquinolones; Greece; Hospitals, University; Humans; Logistic Models; Male; Middle Aged; Prospective Studies; Risk Factors; Time Factors